Optimal allocation of financial resources for ensuring reliable resilience in binary-state network infrastructure - Yeh, Wei-Chang; Zhu, Wenbo (Reliability engineering & system safety, 2024)
•Propose the novel concept of reliable resilience.•Explore the distinctions between reliability, resilience, and reliable resilience.•Proposed the equal-sign BAT for generating all MPs with the same number of arcs.•Propose a novel SLSA to check whether a subgraph is connected.•Apply the concept of reliable resilience to the Taiwan Highway network. In the dynamic landscape of network infrastructures, safeguarding resilience in binary-state systems has emerged as a focal point. This study delves into optimal financial resource allocation strategies to ensure that binary-state networks exhibit consistent and dependable recovery capabilities in the face of adversities, while satisfying the required reliability. Through a comprehensive exploration, we underscore the significance of resilience that is not only robust but also reliable and capable of surviving consecutive breakdowns. By zeroing in on binary-state networks, typified by their components exhibiting either operational or non-operational states, we elucidate strategic measures to fortify their intrinsic recovery mechanisms. Our research introduces a pioneering perspective on the imperative of astute resource distribution to achieve unyielding and trustworthy recovery processes amidst network disturbances. Furthermore, we present an innovative algorithm grounded in the binary-addition-tree algorithm (BAT) and stepwise vectors to adeptly address the problem. This study contributes to the discourse on reliable resilience, a novel form of resilience that enables a system to repeatedly recover from a series of unexpected failures, all within a limited and fixed recovery budget, while maintaining a required reliability and consistency in performance.